Person-Organization Fit and Organizational Engagement in The Nigerian Airspace Management Agency, Port Harcourt - Ugo Chuks Okolie (Journal of Public Administration and Government, 2022)
The Nigerian Airspace Management Agency (NAMA) which is saddled with the core mandate as the nation’s air navigation service provider is the bed rock of Nigeria Aviation Industry and this puts a great demand on the employees who are supposed to developed uniform and consistent Nigerian airspace to meet with international standards and practices. In recent times, employees of the agency have come under verbal attacks by passengers and the general public on accusation of insensitivity in their duties and lack of professionalism. Perhaps, major fallout of this development has been the poor person-organization fit in the sector which resulted into employees’ attitudes and behaviours inimical to organizational engagement, prompt and efficient service delivery. This study therefore examined the effect of person-organization fit on organizational engagement in the Nigerian Airspace Management Agency, Port Harcourt using survey research method. Accidental sampling technique was used to elicit information via questionnaire from 178 respondents. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 21. The results of the study showed that there is significant relationship between person-organization fit and organizational engagement. As predicted, the study also revealed that person-organization exerts a positive and statistically significant effect on organizational engagement in the Nigerian Airspace Management Agency. Thus, the study recommends among others that management should give due attention to person-organization fit which positively contributes to a large number of organizational attitudes and behaviours such as job satisfaction, display of organizational citizenship behaviour, job performance, organizational commitment and engagement.